2020
DOI: 10.18632/aging.102646
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol targets PD-L1 glycosylation and dimerization to enhance antitumor T-cell immunity

Abstract: New strategies to block the immune evasion activity of programmed death ligand-1 (PD-L1) are urgently needed. When exploring the PD-L1-targeted effects of mechanistically diverse metabolism-targeting drugs, exposure to the dietary polyphenol resveratrol (RSV) revealed its differential capacity to generate a distinct PD-L1 electrophoretic migration pattern. Using biochemical assays, computer-aided docking/molecular dynamics simulations, and fluorescence microscopy, we found that RSV can operate as a direct inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 122 publications
(178 reference statements)
3
99
0
Order By: Relevance
“…25,38 Several small molecules, such as 2-deoxyglucose, metformin, and resveratrol, have been shown to cause abnormal PD-L1 glycosylation and induce its ER accumulation or decrease its stability. [39][40][41] Our data that the PD-L1 3NQ glycosylation mutant failed to induce PD-1 degradation in the coculture supported the essentiality of glycosylation for the function of PD-L1 (Figure 4(b)). However, the blockade of PD-L1 ER exporting by BMS1166 was not a consequence of inhibition of PD-L1 glycosylation, because a complete loss of N-glycosylation induced by TM did not affect the ER exporting and membrane localization of PD-L1 ( Figure S5).…”
Section: Discussionsupporting
confidence: 62%
“…25,38 Several small molecules, such as 2-deoxyglucose, metformin, and resveratrol, have been shown to cause abnormal PD-L1 glycosylation and induce its ER accumulation or decrease its stability. [39][40][41] Our data that the PD-L1 3NQ glycosylation mutant failed to induce PD-1 degradation in the coculture supported the essentiality of glycosylation for the function of PD-L1 (Figure 4(b)). However, the blockade of PD-L1 ER exporting by BMS1166 was not a consequence of inhibition of PD-L1 glycosylation, because a complete loss of N-glycosylation induced by TM did not affect the ER exporting and membrane localization of PD-L1 ( Figure S5).…”
Section: Discussionsupporting
confidence: 62%
“…When cancer cells were previously exposed to resveratrol, cytotoxic T-lymphocyte activity was notably exacerbated. These results suggest that resveratrol exerts anti-cancer property by restoring T-cell function [59].…”
Section: Synergistic Effects Of Combined Polyphenols Administrationmentioning
confidence: 78%
“…Another mechanism underlying the antitumor effects of resveratrol could be its regulation of PD-L1 expression in the tumor since previous studies have demonstrated that it reduces PDL1 expression in cancer cells and interferes with PDL1 dimerization and glycosylation. 44 , 45 Thus, resveratrol has a broad impact on antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%